(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article explores the United Nations’ resolute actions in addressing poverty through the lens of the Sustainable Development Goals (SDGs). With poverty persisting as a global challenge, the United Nations has embarked on a transformative journey to eradicate poverty in all its forms and dimensions by 2030. The article highlights the concerted efforts of the United Nations in mobilizing resources, fostering partnerships, and implementing comprehensive strategies to combat poverty. It examines key initiatives undertaken by the United Nations, such as poverty reduction programs, inclusive economic growth, social protection measures, and access to basic services, all aimed at uplifting the lives of the most vulnerable populations. Furthermore, the article delves into the United Nations’ emphasis on promoting sustainable development and tackling the root causes of poverty, including inequality, lack of education, gender disparities, and inadequate access to healthcare. By analyzing the United Nations’ commitment to the SDGs, this article showcases the organization’s multifaceted approach to poverty eradication and highlights the importance of global collaboration in achieving sustainable and inclusive development for all.